Surface enrichment and diffusion enabling gradient-doping and coating of Ni-rich cathode toward Li-ion batteries - Haifeng Yu (Nature Portfolio, 2021)
The commercialisation of promising Ni-rich cathodes is limited by capacity fading and thermal runaway. Here, the authors design a gradient Al-doped and LiAlO2-coated LiNi0.9Co0.1O2 cathode, which addresses the crystal degradation and interfacial instability and thus improves the cycle and thermal stabilities.